Analisa Proses Routing RIPV1, RIPV2, RIPNG, Antara Model IPV4 Dengan IPV6 Pada Jaringan Data PT. Pertamina RU II Dumai - Irsan Fitrah Adhil; Linna Oktaviana Sari; Ery Safrianti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The development of telecommunications today make the need for communication of data quickly and efficiently is also one of his company besar.IPv4 scale to support 32-bit addressing and developed IPv6 supports up to 128 -bit addressing and also developed a routing protocol that works padaIPv6.Routing protocol always to update the routing table, with the use of IPv6 has a huge addressing whether the effect on the quality ofnetwork.Skripsi is structured to determine the Quality of Service of the Routing Information Protocol version 1 , Routing Information Protocol version 2 , and Routing Information Protocol next-generation data networks PT . Pertamina RU II Dumai . Performed using the general network simulator 3 software and software wireshark . Analysis of the results of the design using three perangka trouter counted Quality Of Service obtained the value of total delay RIPv2 routing smaller average 11.2 % of the RIPv1 routing . While smaller RIPng routing of routing RIPv2 19.4 % and 28.5 % smaller than the total packet routing RIPv1.Nilai lossrouting smaller RIPv2 routing RIPv1.Sedangkan 15.9 % from 5.2% RIPng smaller than RIPv2 routing and 20.3 % smaller than RIPv1 routing. The total value of RIPv2 routing throughput greater than routing RIPv1 43.6 % and 63.9 % greater than the total value RIPng.Sedangkan routing throughput greater routing RIPv1 routing RIPng.Dengan 35.9 % compared to the use of six devices total RIPng router routing delay average , total packet loss , and total troghput small compared to most other routing .Keywords: Routing RIPv1, RIPv2, RIPng, IPv4, IPv6, QOS,GNS 3